2000
DOI: 10.4269/ajtmh.2000.62.225
|View full text |Cite
|
Sign up to set email alerts
|

Random distribution of mixed species malaria infections in Papua New Guinea.

Abstract: Abstract. Plasmodium falciparum (Pf), P. vivax (Pv), P. malariae (Pm), and P. ovale (Po) infections are endemic in coastal areas of Papua New Guinea. Here 2,162 individuals living near Dreikikir, East Sepik Province, have been analyzed for complexity of malaria infection by blood smear and polymerase chain reaction (PCR) diagnoses. According to blood smear, the overall prevalence of Plasmodium infection was 0.320. Most individuals (0.283) were infected with a single species only. The prevalence of mixed specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
122
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 40 publications
9
122
0
4
Order By: Relevance
“…In a series of studies from PNG that have combined LM and molecular diagnostics [29,31,32], we have found that molecular methods consistently detected significantly increased prevalence of all four malaria species of humans, with the largest increases in P. malariae and P. ovale. In these studies from three different PNG populations, the prevalence of P. falciparum and P. vivax increased between 1.6 and 3.0-fold and 2.1 and 3.4-fold, respectively, and a 2.6 to 10.9-fold increase in P. malariae prevalence was observed (LM:…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 98%
See 4 more Smart Citations
“…In a series of studies from PNG that have combined LM and molecular diagnostics [29,31,32], we have found that molecular methods consistently detected significantly increased prevalence of all four malaria species of humans, with the largest increases in P. malariae and P. ovale. In these studies from three different PNG populations, the prevalence of P. falciparum and P. vivax increased between 1.6 and 3.0-fold and 2.1 and 3.4-fold, respectively, and a 2.6 to 10.9-fold increase in P. malariae prevalence was observed (LM:…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 98%
“…Detection of P. ovale by LM ranged from 0 to 0.3%, whereas LDR-FMA detected P. ovale infection in 5.2 to 15.6% of the study subjects. Overall, the majority of P. malariae and P. ovale diagnoses have been observed in the context of mixed infections with P. falciparum and/or P. vivax, including several quadruple infections [29,31,32]. Therefore, it is likely that P. malariae, P. ovale and mixed species infections are substantially more common in PNG than previously thought.…”
Section: Improved Diagnosis Of P Malariae and P Ovale Infections Bymentioning
confidence: 99%
See 3 more Smart Citations